Lower body mass index potentiates the association between skipping breakfast and prevalence of proteinuria - Muratsu, Jun; Kamide, Kei; Fujimoto, Takashi; Takeya, Yasushi; Sugimoto, Ken; Taniyama, Yoshiaki; Morishima, Atsuyuki; Sakaguchi, Katsuhiko; Rakugi, Hiromi (Frontiers in Endocrinology, 2022)
Background: Proteinuria is an important predictor of cardiovascular disease and mortality. Several studies reported the association between skipping breakfast and the prevalence of proteinuria. Furthermore, skipping breakfast was associated with an increased risk of obesity. Although proteinuria is highly prevalent in obese, the association between the prevalence of proteinuria and low body mass index (BMI) was reported in previous cross-sectional study in asymptomatic individuals without known kidney diseases. The aim of this cross-sectional study was to assess the clinical impact of BMI on the association between skipping breakfast and the prevalence of proteinuria in normal renal function subjects. Methods: The present study included 26,888 subjects (15,875 males and 11,013 females) with an estimated glomerular filtration rate ≥ 60 mL/min/1.73 m2 and no history of kidney disease who underwent a health checkup in Sumitomo Hospital. The association between skipping breakfast and the prevalence of proteinuria (defined as dipstick proteinuria of ≥ 1+) was assessed using logistic regression models adjusted for clinically relevant factors. Results: Skipping breakfast was reported in 3,306 males (20.8%) and 1,514 females (13.8%). Multivariable adjusted logistic regression models showed that skipping breakfast was significantly associated with prevalence of proteinuria above 1+. This association was evident in lower BMI subjects, even after adjusting for clinically relevant factors (adjusted odds ratios of male and female were 1.67 [1.17-2.38] and 1.92 [1.31-2.82], respectively), whereas this association was not evident in higher BMI subjects. Conclusion: The proteinuria in lower BMI subjects might be needed to be careful about skipping breakfast.